Building Entrepreneurship Culture in Madrasah Actor-Network Theory Bruno Latour Perspective - Marjuni Marjuni (Basic and Applied Education Research Journal, 2020)
This paper questions how the strategy of developing entrepreneurship culture in Madrasah? and how to realize the entrepreneurship culture in Madrasah based on the perspective of Bruno Latour's Actor Networks Theory (ANT)? From the results of the literature review, it can be concluded that the strategy for developing entrepreneurship culture in Madrasah can be done with the Fife Ps approach, namely: Plan, Pattern, Position, Perspective, and Ploy. The Actor Networks Theory (ANT) approach can be used by Madrasah principals to maximize The Five Ps Strategy Approach in building madrasah entrepreneurship culture. The ability of Madrasah principals to organize Madrasah in achieving common goals using a behavioral approach based on The Five P Strategy madrasah residents by optimizing risk, innovating to take advantage of opportunities, taking personal responsibility and managing changes in the madrasah environment dynamically, effectively and efficiently into prerequisites for creating a culture of entrepreneurship in Madrasah. The Actor Networks Theory approach was chosen because it offers a new perspective to madrassah in proportionally positioning human and non-human resources.